Purchase and consumption habits of Terrincho PDO Cheese: the consumer perspective in the municipality of Bragança, Portugal - Perinoto, Larissa Caroline (2020)
Trás-os-Montes region presents a range of certified products with high cultural and commercial value such as Terrincho Protected Designation of Origin (PDO) cheese, which is manufactured with milk of the Churra sheep from Terra Quente. The aim of this research was to define the consumer profile of Terrincho PDO cheese, as well as its purchasing and consumption habits. To achieve these objectives, an analytical and cross-sectional research was developed. To collect the data, a structured questionnaire was applied through personal interviews. The respondents were approached, at random, in public spaces of Bragança city between March 1th and 27th, 2019. Of the 380 interviewees, 57 were consumers of Terrincho PDO cheese. These consumers were mainly female (56%), with an average age of 58.3 years (± 16.190), married (70%), active (50%), lived in the municipality of Bragança (90%) with 2 (40% %) or 3 (28%) people in their household. Consumers of Terrincho PDO cheese differ significantly (p-value < 0.05) from non-consumers because they had a higher education degree (53%), a monthly household income above 1200 euros and were retired (47%). The frequency of consumption of the product occurred once a month (33%) or two to four times a year (26%), while the purchase frequency occurred on a monthly basis (69%). At the time of the purchase, most of the interviewees opted for the certified product (67%) due to the safety (79%) that it represents. Terrincho PDO cheese is a product capable to generate high added-value contributing to the economic development of Trás-os-Montes region given its acceptance by consumers.